2001
DOI: 10.1002/1097-4636(20010605)55:3<424::aid-jbm1032>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biological evaluation of endotoxin contamination on natural rubber latex products

Abstract: Relationship between pyrogenicity and bacterial endotoxin contamination on latex products was demonstrated by chemical analysis and biological assays. In commercially available latex products' surveillance, water extracts prepared from one surgical glove and two silicone elastomer-coated Foley catheters sterilized by gamma-irradiation were obviously pyrogenic in rabbits. The induced fever was monophasic at low dose of the pyrogenic extracts and biphasic at high dose. These extracts exhibited limulus amebocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…It has been shown that LPS is only extractable to a certain extent, while residuals stick on the surface and thus cannot be detected by the pyrogen-testing procedures mentioned above. [11][12][13][14] Furthermore, it has also been shown that the inflammatory capacity of some pyrogens can increase when they are bound on surfaces compared to the cytokine release evoked by pyrogens in the liquid state; 15 consequently, this can lead to the underestimation of possible risks when testing eluates.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that LPS is only extractable to a certain extent, while residuals stick on the surface and thus cannot be detected by the pyrogen-testing procedures mentioned above. [11][12][13][14] Furthermore, it has also been shown that the inflammatory capacity of some pyrogens can increase when they are bound on surfaces compared to the cytokine release evoked by pyrogens in the liquid state; 15 consequently, this can lead to the underestimation of possible risks when testing eluates.…”
Section: Introductionmentioning
confidence: 99%
“…fever inducing substances. This means that a device may be sterile but still pyrogenic, as it has been shown in several studies [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Heat‐sacrificed bacterial cells were collected by centrifugation (7000 g, 15 min) and washed three times with distilled water followed by sequential extraction with ethanol, acetone, and diethyl ether to dehydrate the cells. Endotoxin was extracted from the dried cells of the E. coli O3:K2a,K2b:H3 ATCC strain by the phenol‐water method, and purified by repeated ultracentrifugation after deoxyribonuclease and ribonuclease treatments . The endotoxin activities of the purified endotoxin and the dried E. coli 0111 cells were 27.5 and 0.159 EU/ng, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Endotoxin was extracted from the dried cells of the E. coli O3:K2a,K2b:H3 ATCC strain by the phenol-water method, 18 and purified by repeated ultracentrifugation after deoxyribonuclease and ribonuclease treatments. 19 The endotoxin activities of the purified endotoxin and the dried E. coli 0111 cells were 27.5 and 0.159 EU/ng, respectively. Endotoxin was present as a contaminant in the dried S. aureus cells at 0.48 EU/mg.…”
Section: Preparation Of Endotoxin and Bacterial Cellsmentioning
confidence: 99%